Discharge Outcomes and Survival of Patients with Advanced Cancer Admitted to an Acute Palliative Care Unit at a Comprehensive Cancer Center - Hui, David (Mary Ann Liebert, Inc., 2010)
BACKGROUND: Acute palliative care units (APCUs) are new programs aimed at integrating palliative and oncology care. Few outcome studies from APCUs are available. OBJECTIVES: We examined the frequency, survival, and predictors associated with home discharge and death in our APCU. METHODS: All patients discharged from the APCU between September 1, 2003 and August 31, 2008 were included. Demographics, cancer diagnosis, discharge outcomes, and overall survival from discharge were retrieved retrospectively. RESULTS: The 2568 patients admitted to APCU had the following characteristics: median age, 59 years (range, 18–101); male, 51%; median hospital stay, 11 days; median APCU stay, 7 days; and median survival 21 days (95% confidence interval [CI] 19–23 days). Five hundred ninety-two (20%), 89 (3%), and 1259 (43%) patients were discharged to home, health care facilities, and hospice, respectively, with a median survival of 60, 29, and 14 days, respectively (p < 0.001). Nine hundred fifty-eight (33%) patients died during admission (median stay, 11 days). Compared to hospice transfers, home discharge (hazard ratio = 0.35, 95% CI 0.30–0.41, p < 0.001) was associated with longer survival in multivariate analysis, with a 6-month survival of 22%. Multivariate logistic regression revealed that male gender, specific cancer primaries, and admissions from oncology units were associated with death in the APCU, while younger age and direct admissions to the APCU were associated with home discharge. CONCLUSIONS: Our APCU serves patients with advanced cancer with diverse clinical characteristics and survival, and discharged home a significant proportion with survival greater than 6 months. Results from this simultaneous care program suggest a pattern of care different from that of traditional hospice and palliative care services.